HUBUNGAN ANTARA PRESENTASI DIRI ONLINE DENGAN KETERGANTUNGAN EMOSIONAL DALAM RELASI ONLINE PADA MAHASISWA DI BANDAR LAMPUNG: PERAN MEDIASI KESEPIAN - Virliyati Afiyah Intani; Shinta Pratiwi; Mulya Virgonita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to explore the relationship between online self-presentation and emotional dependency in online relationships among university students in Bandar Lampung, examining the mediating role of loneliness between both variables. Using a phenomenological approach grounded in bottom-up methodology, this research integrates qualitative and quantitative methods (mixed methods). In the qualitative phase, in-depth interviews were conducted with 12 purposively selected students to understand their lived experiences regarding self-presentation on digital platforms. Qualitative findings were then used to construct hypotheses and measurement instruments in the quantitative phase involving 247 students from various universities in Bandar Lampung. Quantitative data were analyzed using structural equation modeling (SEM) with bootstrapping to test the mediation effect. Results indicate that idealized online self-presentation positively and significantly correlates with emotional dependency (β = 0.42; p < .001). Loneliness was found to partially mediate this relationship (indirect effect = 0.18; 95% CI [0.09; 0.28]). Phenomenological findings reveal that students construct digital identities as a compensatory mechanism for feelings of social rejection in physical environments, ultimately reinforcing cycles of emotional dependency in virtual relationships. The implications of this study are relevant for developing campus-based digital literacy programs and psychological interventions.